Perubahan Kepemilikan Manajerial dan Perubahan Nilai Perusahaan - Madyan, Muhammad; Pratiska, Riska Gita; Kholidah, Himmatul (Forum Manajemen Indonesia (FMI), 2018)
Managerial ownership is an important element in reducing the agency conflict that occurs in a firm. The ownership can provide manager’s incentives to perform optimally in achieving the firm’s goal to improve firm value. Managers in each firm will adjust their ownership to respond firm value. That adjustment can create a changes in managerial ownership. This study aims to examine the relation between changes in managerial ownership to changes in firm value that used a non-financial firms from 2009-2011 as a sample. The results show that  negative  changes  on  managerial  ownership  have  a  negative  and  significant  to changes in firm value, while positive changes on managerial ownership have a positive and not significant to changes in firm value.   Keywords: Managerial ownership, changes in managerial ownership, and changes in firm value